Prevalence of Depressive Disorder among Patients with Epilepsy: a cross-sectional study - Devkota, Anup; Ghimire, Sapana; Thapa, Sheela (Journal of Karnali Academy of Health Sciences, 2021)
Background: Epilepsy is the most common neurological disease in the general population. Depression when comorbid in individuals with epilepsy contributes to low quality of life. As the epilepsy clinics do not routinely assess for major depression substantial opportunity exists to improve the quality of care for many people with epilepsy. The objective of the study was to study the prevalence of depressive disorder and associated factors in individuals with epilepsy. Methods: A cross-sectional study was conducted at the teaching hospital of Karnali Academy of Health Sciences, Jumla. Sixty patients with epilepsy meeting the inclusion criteria of the study were enrolled in the study. Data was collected using Patient Health Questionnaire-9 (PHQ-9) via face-to-face interview. Descriptive statistics was presented as frequency and percentages. Association between variables was assessed with Chi-square test. P-value of <0.05 was considered as statistically significant. Results: The mean age of the participants in years was 32.45 (± SD 10.39). Majority of the participants were married (80%) and between 25-34 years of age (33.3%). Among the participants, 33.3% were farmers and 8.3% were housewives by occupation. The majority of the participants were literate (38.3%) and male (65%). The prevalence of depression was 55%. Various variables like age, sex, caste, education and occupation showed no association with depression. Conclusion: The prevalence of depression was more than half in individuals with epilepsy. The study recommends for screening of depressive disorder among individuals with epilepsy by attending clinicians on a regular basis.